2018
DOI: 10.1080/21691401.2018.1491475
|View full text |Cite
|
Sign up to set email alerts
|

Controlled formation of polylysinized inner pores in injectable microspheres of low molecular weight poly(lactide-co-glycolide) designed for efficient loading of therapeutic cells

Abstract: This study aimed to develop porous microspheres with a suitable porous structure and mechanical property for cell delivery using a comparatively low molecular weight (MW) poly(lactide-co-glycolide) (PLGA) having a weak mechanical strength and fast degradation rate, which could be potentially used for treatment of corneal endothelial diseases. Porous microspheres of 30 kDa PLGA with different pore sizes were prepared by varying preparation conditions, and the microspheres with mean pore diameters approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…PLGA MS prepared using the inner aqueous phase devoid of ammonium bicarbonate exhibited few pores on their surface, whereas the MS fabricated using ammonium bicarbonate solutions showed numerous and large pores ( Figure 1). The number of pores on the surface of the MS and the pore sizes were greater when the concentration of ammonium bicarbonate in the inner aqueous phase was higher, which was consistent with the findings of previous studies [34,48,49]. The uniformity of pore structure decreased with increasing the concentration of ammonium bicarbonate in the inner aqueous phase (Figure 1).…”
Section: Surface Morphology and Pore Characteristics Of Porous Plga Mssupporting
confidence: 90%
See 4 more Smart Citations
“…PLGA MS prepared using the inner aqueous phase devoid of ammonium bicarbonate exhibited few pores on their surface, whereas the MS fabricated using ammonium bicarbonate solutions showed numerous and large pores ( Figure 1). The number of pores on the surface of the MS and the pore sizes were greater when the concentration of ammonium bicarbonate in the inner aqueous phase was higher, which was consistent with the findings of previous studies [34,48,49]. The uniformity of pore structure decreased with increasing the concentration of ammonium bicarbonate in the inner aqueous phase (Figure 1).…”
Section: Surface Morphology and Pore Characteristics Of Porous Plga Mssupporting
confidence: 90%
“…After the degradation, the monomers are further metabolized and subsequently eliminated from the body. Our previous work also showed that most of the PLGA MS, designed for a cell delivery system, composed of PLGA of a low molecular weight (30 kDa) and an equal L/G ratio degraded within 12 weeks [34]. It was also reported that the formulation composed of PLGA of a high molecular weight (135 kDa) and an equal L/G ratio degraded more than 90% of the PLGA Morphological changes were also observed in each formulation during the in vitro release experiment (Figure 6b).…”
Section: In Vitro Releasementioning
confidence: 89%
See 3 more Smart Citations